Analisis Pelaksanaan Pengodean Tindakan Medis Pasien JKN di RSI Siti Rahmah Padang - Mardiawati, Dewi; Leonard, Devid (Jurnal Endurance, 2019)
Claim process proposed by a hospital, there were still returned claim documents verification of BPJS, in which medical treatment codes were not corrected. The problem was that in implementation of coding application could influence the health cost service. A goal of the research was to expose the problem of coding application in medical treatment through analysis process of input and output factors. A kind of the research was qualitative with case study approach. This research was conducted at Islamic Hospital of Siti Rahmah of Padang from February to July 2017. The research informants were about 6 persons taken with a technique of purpose sampling. The analysis of result data were from detailed interview sourced from coding data reduction to be transcription. Category of providing data, interpretation. The research result showed that  medical treatment disturbance of coding  implementation was not clearness of doctor’s writing as icon of medical diagnose and incomplete resume sent. Computer coding system  was not maximal because of the new  medical record officers. Hospital officer added the strength in policy regulation  in human resources through increasing life skill such as training. The policy strength must be fixed regulation rewards and sanction for medical recorder not fulfilling the un accurate data. Besides, socialization from medical record unit about importance of medical diagnose treatment furthermore it relates with an implementation of SOP through regular watch.Pada proses pengajuan klaim di rumah sakit masih terdapat berkas yang dikembalikan verifikator BPJS, salah satu penyebab dikarenakan kode tindakan medis tidak tepat. Permasalahan pelaksanaan tindakan pengodean dan tindakan medis dapat mempengaruhi tarif pelayanan kesehatan. Tujuan penelitian adalah mengeksplorasi permasalahan pelaksanaan pengodean tindakan medis dengan menganalisis faktor input, proses dan output. Jenis penelitian adalah kualitatif dengan pendekatan studi kasus. Penelitian dilakukan di RSI Siti Rahmah Padang dari bulan Februari sampai Juli 2017. Informan peneltian ini berjumlah 6 orang diambil dengan teknik purposive sampling, Analisis data hasil wawancara mendalam dengan tahap transkripsi, reduksi, coding, kategori, penyajian dan interpretasi data. Hasil penelitian menunjukkan yang menghambat kelancaran pelaksanaan pengodean tindakan medis adalah ketidak jelasan tulisan dokter sebagai penegak diagnosa dan tindakan medis serta ketidak lengkapan pengisian resume. Pengodean disistem komputerisasi belum maksimal karena petugas koding masih baru. Sebaiknya rumah sakit melakukan penguatan input, dibidang SDM dengan meningkatkan keterampilan melalui pelatihan. Penguatan kebijakan melalui regulasi dan sanksi tegas bagi SDM yang tidak mengisi rekam medis dengan baik dan benar, serta perlu sosialisasi tentang pentingnya pengisian diagnosa tindakan medis sesuai kaidah ICD 9 CM dan Penguatan fungsi manajemen dalam pelaksanaan pengodean tindakan medis terutama berkaitan dengan SOP pelaksanaan melalui kegiatan pengawasan secara berkala.